2016
DOI: 10.1371/journal.pone.0162013
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Expansion of WRKY Gene Family in Banana and Its Expression Profile during the Infection of Root Lesion Nematode, Pratylenchus coffeae

Abstract: The WRKY family of transcription factors orchestrate the reprogrammed expression of the complex network of defense genes at various biotic and abiotic stresses. Within the last 96 million years, three rounds of Musa polyploidization events had occurred from selective pressure causing duplication of MusaWRKYs with new activities. Here, we identified a total of 153 WRKY transcription factors available from the DH Pahang genome. Based on their phylogenetic relationship, the MusaWRKYs available with complete gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Comparison of the number of WRKY genes in pineapple with other sequenced monocot genomes has shown that pineapple possesses comparatively lesser number of genes [ 34 , 43 ā€“ 45 ]. Tandem and segmental duplication events have played a critical role in the expansion of WRKY gene family [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the number of WRKY genes in pineapple with other sequenced monocot genomes has shown that pineapple possesses comparatively lesser number of genes [ 34 , 43 ā€“ 45 ]. Tandem and segmental duplication events have played a critical role in the expansion of WRKY gene family [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result was similar to a previous study which reported that defense was built up in a resistant coffee accession before leaf miner ( Leucoptera coffella ) attack 38 . Among the 3,867 DEGs, it is worth mentioning that the most enriched KEGG pathway belonged to plant-pathogen interaction and was composed on 7 WRKY transcription factors known to play an important role in biotic stress resistance 39ā€“41 . Interestingly, 12 out of the 51 TIFY transcription factors contained in the banana genome were also differentially expressed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, WRKY70 increased plant susceptibility to necrotrophic fungal pathogens because it acts as a repressor of jasmonate-regulated genes 71 . A total of 153 WRKY transcription factors were identified in the DH Pahang genome 25,41 . It was found that a large number (56) of WRKY genes showed inducible expression in banana root tissue during Foc infection 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Interesting, PtrWRKY18 (Populus trichocarpa, Ptr) and PtrWRKY35 activate pathogenesis-related (PR) genes, and increase the resistance to the biotrophic pathogen Melampsora [23]. In the banana, MaWRKY69 and MaWRKY92 are highly upregulated in the susceptible cultivar, but downregulated in the resistant cultivar after infection by the root lesion nematode Pratylenchus coffeae [24]. MaWRKY71-overexpressing transgenic bananas have increased salt and oxidative stress resistance compared to wild-type bananas, with no effect on the disease resistance against Foc [25].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that MaWRKY31, MaWRKY33, MaWRKY60, and MaWRKY71 directly bind to the W-box elements in the promoters of 9-cis-epoxycarotenoid dioxygenase 1 (MaNCED1) and MaNCED2 and activate their expression, thereby regulating abscisic acid-induced cold tolerance in banana fruit [27]. Although MaWRKYs are comprehensively identified in the banana, the in vivo roles remain elusive [9,24], and need to be investigated further.…”
Section: Introductionmentioning
confidence: 99%